Bidirectional disruption of GNAS transcripts causes broad methylation defects in pseudohypoparathyroidism type 1B - Yorihiro Iwasaki; Monica Reyes; Anna Ryabets-Lienhard; Barbara Gales; Agnès Linglart; Danny E. Miller; Isidro B. Salusky; Murat Bastepe; Harald Jüppner (Proceedings of the National Academy of Sciences, 2025)
Pseudohypoparathyroidism type 1B (PHP1B) is a multihormone resistance disorder caused by aberrant GNAS methylation. Characteristic epigenetic changes at GNAS differentially methylated regions (DMRs), i.e., NESP, AS1, AS2, XL, and A/B, are associated with specific structural defects in different autosomal dominant PHP1B (AD-PHP1B) subtypes. However, mechanisms underlying abnormal GNAS methylation remain incompletely defined, largely because viable PHP1B mouse models are lacking. Using lymphoblastoid cells and induced pluripotent stem cells, we show that various GNAS methylation patterns in PHP1B reflect differential disruption of sense and antisense GNAS transcripts. In cases with broad GNAS methylation changes, loss of the maternal, sense-transcribed exon H/AS region impairs methylation of the AS1 DMR, which results in biallelic expression of an antisense transcript, GNAS-AS1 , and NESP hypermethylation. In contrast, cases with normal AS1 methylation, including STX16 deletions, show monoallelic GNAS-AS1 expression and normal NESP methylation. The roles of these GNAS transcripts were confirmed by a retrotransposon in GNAS-AS1 intron 1, identified in an AD-PHP1B family. This insertion impaired exon H/AS transcription when located on the maternal allele, thus preventing the complete establishment of methylation at all maternal GNAS DMRs, leading to biallelic GNAS-AS1 transcription. However, maternal GNAS-AS1 transcription was profoundly attenuated, thus allowing only a small gain-of-methylation at NESP. Likewise, on the paternal allele, the retrotransposon attenuated GNAS-AS1 transcription, thus preventing complete NESP methylation. Our findings support a model of bidirectional transcription-mediated regulation of methylation at GNAS DMRs and will help to refine systematic approaches for establishing molecular defects underlying different PHP1B subtypes.